PENGARUH KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAIPADA DINAS PERHUBUNGAN KABUPATEN LAMPUNG SELATAN - Kuswarak - (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2020)
Work discipline is very necessary to be applied to a government institution. Because by applying the provisions set by the organization whose form of regulation will direct employees to act according to the wishes of the organization. The purpose of this study is to find out the Effect of Work Discipline andWork Competence on Employee Performance at the South Lampung District Transportation Service to the population as respondents. Methods of collecting data as primary data through observation, interview and questionnaire and secondary data.Based on the regression equation the results of hypothesis testing have proven that there is an influence between work discipline and employee performance. testing the work motivation hypothesis shows the value of t count of -0.243 with a significance level of 0.720. The significance level is greater than 0.05, which means that the hypothesis in this study accepts Ho and rejects Ha. Thus it can mean that the H1 hypothesis "work discipline" does not have a positive influence on Employee Performance "rejected.The results ofhypothesis testing have proven that there is an influence between work motivation and employee performance. The test proves that the results of testing the work motivation hypothesis show the value of t count of 4.505 with a significance level of 0,000. The significance level of the result of 0,000 is smaller than 0.05, which means that the hypothesis in this study accepts Ha and rejects Ho. Thus it can mean that the H2 hypothesis "work motivation has a positive effect on employee performance" is accepted.